Annona muricata leaf extracts obtained with subcritical water and conventional methods: evaluation of antioxidant activities, total polyphenol and rutin contents - Santos, Ronald Keverson da Silva; Silva Junior, Reinaldo Alves da; Ferreira, Magda Rhayanny Assunção; Soares, Luiz Alberto Lira; Stragevitch, Luiz; Danielski, Leandro (Acta Scientiarum. Technology, 2022)
Annona muricata (soursop) is a native American plant and is well known for its leafy canopy and its fruits, widely consumed in South America and Southeast Asia. The objective of this work was to obtain Annona muricata leaf extracts and to evaluate their antioxidant activities, which were obtained by four different extraction methods: Soxhlet, maceration, ultrasound, and pressurized hot (subcritical) water. In order to assess and compare the extracts bioactivities, total polyphenol contents of the extracts were evaluated by the Folin-Ciocalteu method and the antioxidant activities were determined by DPPH and ABTS methods. High performance liquid chromatography was used to identify and quantify rutin, a special flavonoid, which was found to be the most representative component, for all extracts obtained. Rutin is known for its benefits has a potential natural antioxidant. Among all extraction methods investigated, extracts obtained by the Soxhlet method using ethanol as solvent showed a higher total polyphenol content, 2.83% of gallic acid equivalent/g plant material, as well as higher antioxidant activity. A correlation between rutin content and antioxidant activity was found. Soxhlet extractions revealed samples with the highest rutin content of 0.130 Â± 0.003 g g-1, what may explain the high antioxidant activity of the obtained A. muricata leaf extracts.